Carinian network contributions to digital preservation in institutional digital repositories: the UFRN case - Silva, Mayane Paulino de Brito e; Moura, Rafaela Karoline Galdencio de; Siebra, Sandra de Albuquerque; Pinto, Virgínia Bentes (Informação em Pauta, 2019)
It discusses about the contributions of the Rede Cariniana in the range of digital preservation on Institutional Digital Repositories. It uses as methodology the instruments which are necessary to the development of a bibliographic, exploratory and descriptive research, with a qualitative approach. It uses a study case in the Institutional Digital Repository from UFRN through a data collection that was made through a semistructured interview. It approaches reflections and concepts related to the digital preservation, which is understood as a set of actions and techniques responsible in the scope of digital information, by allowing that it can be preserved and recovered throughout time. It mentions the Rede Cariniana, which offers diverse alternatives to Brazilian entities in order to collect, store and promote the access to the selected content through authorized copies. It points that the process of connection between the electronic science and the need of digital data preservation would be based on the Institutional Digital Repositories. It presents as results the guaranty of the storage as the main interest in the adoption of tools directed to the digital preservation of documents; the UFRN is part of the study realized by the Rede Cariniana, which hosts the scientific typology, whose documental growth may come to be 3000 per year and aims to gather all the scientific material in the next 5 years, considering the technological and human aspects, as well as the pratical action off a digital preservation policy. Thus, the research concludes that the purpose of enriching and contributing to the initiatives and practices about the Brazilian digital preservation is very much promoted by the Rede Cariniana, through a decentralized infrastructure, by using resources of distributed computing.